2022
DOI: 10.3390/ijms23063370
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Active CD11b Monocytes in Blood and Disease Progression in Amyotrophic Lateral Sclerosis

Abstract: Monocytes expressing the inflammation suppressing active CD11b, a beta2 integrin, may regulate neuroinflammation and modify clinical outcomes in amyotrophic lateral sclerosis (ALS). In this single site, retrospective study, peripheral blood mononuclear cells from 38 individuals living with ALS and 20 non-neurological controls (NNC) were investigated using flow cytometry to study active CD11b integrin classical (CM), intermediate (IM) and non-classical (NCM) monocytes during ALS progression. Seventeen ALS parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…According to literature, healthy individuals typically have only 1–5% of activated CD11b in the ‘open’ conformation in their peripheral blood, whereas patients with tumor burdens may have 10–30%. 35 Based on this information, we believe that our findings are supported, demonstrating that BG34-200 can directly, effectively, and specifically target tumor-associated CD11b + inflammatory monocytes by engaging with the activated CD11b in the open conformation I domain.…”
Section: Resultssupporting
confidence: 67%
“…According to literature, healthy individuals typically have only 1–5% of activated CD11b in the ‘open’ conformation in their peripheral blood, whereas patients with tumor burdens may have 10–30%. 35 Based on this information, we believe that our findings are supported, demonstrating that BG34-200 can directly, effectively, and specifically target tumor-associated CD11b + inflammatory monocytes by engaging with the activated CD11b in the open conformation I domain.…”
Section: Resultssupporting
confidence: 67%
“…However, confirmation by larger multi‐centre studies for most putative biomarkers is lacking 82 . A recent study reported a steep increase of monocyte cells expressing the inflammation suppressing active CD11b integrin in blood from patients with ALS, with a slow disease progression 99 . The observation of a peripheral rise of myeloid cells is in line with the reported longitudinal increase of neurotrophin receptor p75 extracellular domain (p75ECD) in urine, from patients with ALS compared to healthy controls.…”
Section: Utilisation Of Blood Biomarkers In Alsmentioning
confidence: 96%
“…Together with the above mentioned limitation, the increase in classical monocytes and the reduction in intermediate monocytes in patients treated with rapamycin, is even more difficult to interpret because of the uncertainty on their role in ALS, and if monocyte subsets and activation profiles are altered depending on the stage of the disease (i.e. the changes are a response to disease and their changes suggest that the immune system becomes more activated as the disease progresses) or if they are instead pathogenetic deserves further studies [25][26][27] .…”
Section: Discussionmentioning
confidence: 99%